2011
DOI: 10.1097/aln.0b013e318215e254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Tidal Volume Ventilation on Time to Extubation in Cardiac Surgical Patients

Abstract: Background Low tidal volumes have been associated with improved outcomes in patients with established acute lung injury. The role of low tidal volume ventilation in patients without lung injury is still unresolved. We hypothesized that such a strategy in patients undergoing elective surgery would reduce ventilator-associated lung injury and that this improvement would lead to a shortened time to extubation Methods A single-center randomized controlled trial was undertaken in 149 patients undergoing elective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 34 publications
1
63
0
4
Order By: Relevance
“…Early extubation, generally considered to be that which is performed during the first 6-8 hours once the preoperative homeostatic state has been reestablished (40), offers a substantial advantage in terms of accelerated recovery, shorter intensive care unit and hospital stay, suggesting that efforts to reduce extubation time are cost-effective (65). Cardiac surgical patients in whom low tidal volumes are administered are more likely to undergo early extubation (37.3% vs. 20.3%; P=0.02) and less likely to require re-intubation (1.3% vs. 9.5%; P=0.03) (66). Safety and efficacy of fast-track care in patients undergoing cardiac surgery was brilliantly assessed by Zhu and colleagues (67) who showed no statistically significant difference in mortality between early and conventional extubation in patients considered to be at low to moderate risk.…”
Section: Non-surgical Techniquesmentioning
confidence: 98%
“…Early extubation, generally considered to be that which is performed during the first 6-8 hours once the preoperative homeostatic state has been reestablished (40), offers a substantial advantage in terms of accelerated recovery, shorter intensive care unit and hospital stay, suggesting that efforts to reduce extubation time are cost-effective (65). Cardiac surgical patients in whom low tidal volumes are administered are more likely to undergo early extubation (37.3% vs. 20.3%; P=0.02) and less likely to require re-intubation (1.3% vs. 9.5%; P=0.03) (66). Safety and efficacy of fast-track care in patients undergoing cardiac surgery was brilliantly assessed by Zhu and colleagues (67) who showed no statistically significant difference in mortality between early and conventional extubation in patients considered to be at low to moderate risk.…”
Section: Non-surgical Techniquesmentioning
confidence: 98%
“…Nevertheless, Cai et al showed that applying ventilation with V T of 6 ml/kg alone was associated with no diff erence in the amount of atelectasis compared to ventilation with V T of 10 ml/kg [27] and application of PEEP may additionally counteract this eff ect [24]. Several studies have shown that protective ventilation can improve lung mechanics, gas exchange and decrease the incidence of postoperative pulmonary complications [24], [25], [28] (Table 1). To better investigate the impact of protective ventilation itself involving low V T or PEEP and recruitment maneuvers, a large RCT including 900 patients and investigating the eff ect on postoperative pulmonary complications of an open lung strategy with high PEEP and recruitment maneuvers in short term mechanical ventilation has recently been completed (PROVHILO) [29].…”
Section: In Surgerymentioning
confidence: 99%
“…Sundar et al 50 examined the time to extubation for cardiac surgical subjects receiving either 6 mL/kg or 10 mL/kg PBW. They found that, although the time to extubation did not significantly decrease, significantly more subjects in the lower V T group were extubated and breathing without assistance 6 -8 h after surgery.…”
Section: Ventilation Of Surgical Patientsmentioning
confidence: 99%